Discovery of N-(piperidin-3-yl)-N-(pyridin-2-yl)piperidine/piperazine-1-carboxamides as small molecule inhibitors of PCSK9. Issue 23 (15th December 2018) - Londregan, Allyn T.; Aspnes, Gary; Limberakis, Chris; Loria, Paula M.; McClure, Kim F.; Petersen, Donna N.; Raymer, Brian; Ruggeri, Roger B.; Wei, Liuqing; Xiao, Jun; Piotrowski, David W.
Graphical abstract: Highlights: A new series of small molecules have been identified as PCSK9 mRNA translation inhibitors. Compounds4d and4g exhibit improved PCSK9 potency, ADME properties, and in vitro safety profiles when compared to earlier leads. Small molecule PCSK9 inhibitors may be effective in the treatment of hypercholesterolemia. Abstract: A series of N-(piperidin-3-yl)-N-(pyridin-2-yl)piperidine/piperazine-1-carboxamides were identified as small molecule PCSK9 mRNA translation inhibitors. Analogues from this new chemical series, such as4d and4g, exhibited improved PCSK9 potency, ADME properties, and in vitro safety profiles when compared to earlier lead structures.